Cartilage-derived cells display heterogeneous pericellular matrix synthesis in agarose microgels - Marloes van Mourik; Bart M. Tiemeijer; Maarten van Zon; Florencia Abinzano; Jurjen Tel; Jasper Foolen; Keita Ito (Matrix Biology Plus, 2024)
The pericellular matrix (PCM) surrounding chondrocytes is essential for articular cartilage tissue engineering. As the current isolation methods to obtain chondrocytes with their PCM (chondrons) result in a heterogeneous mixture of chondrocytes and chondrons, regenerating the PCM using a tissue engineering approach could prove beneficial. In this study, we aimed to discern the behavior of articular chondrocytes (ACs) in regenerating the PCM in such an approach and whether this would also be true for articular cartilage-derived progenitor cells (ACPCs), as an alternative cell source. Bovine ACs and ACPCs were encapsulated in agarose microgels using droplet-based microfluidics. ACs were stimulated with TGF-β1 and dexamethasone and ACPCs were sequentially stimulated with BMP-9 followed by TGF-β1 and dexamethasone. After 0, 3, 5, and 10 days of culture, PCM components, type-VI collagen and perlecan, and ECM component, type-II collagen, were assessed using flow cytometry and fluorescence microscopy. Both ACs and ACPCs synthesized the PCM before the ECM. It was seen for the first time that synthesis of type-VI collagen always preceded perlecan. While the PCM synthesized by ACs resembled native chondrons after only 5 days of culture, ACPCs often made less well-structured PCMs. Both cell types showed variations between individual cells and donors. On one hand, this was more prominent in ACPCs, but also a subset of ACPCs showed superior PCM and ECM regeneration, suggesting that isolating these cells may potentially improve cartilage repair strategies.